Characterization of Bacillus cereus Isolates Associated with Fatal Pneumonias: Strains Are Closely Related to Bacillus anthracis and Harbor B. anthracis Virulence Genes - Hoffmaster, Alex R. (American Society for Microbiology, 2006)
Bacillus cereus is ubiquitous in nature, and while most isolates appear to be harmless, some are associated with food-borne illnesses, periodontal diseases, and other more serious infections. In one such infection, B. cereus G9241 was identified as the causative agent of a severe pneumonia in a Louisiana welder in 1994. This isolate was found to harbor most of the B. anthracis virulence plasmid pXO1 (13). Here we report the characterization of two clinical and one environmental B. cereus isolate collected during an investigation of two fatal pneumonia cases in Texas metal workers. Molecular subtyping revealed that the two cases were not caused by the same strain. However, one of the three isolates was indistinguishable from B. cereus G9241. PCR analysis demonstrated that both clinical isolates contained B. anthracis pXO1 toxin genes. One clinical isolate and the environmental isolate collected from that victim's worksite contained the cap A, B, and C genes required for capsule biosynthesis in B. anthracis. Both clinical isolates expressed a capsule; however, neither was composed of poly-d-glutamic acid. Although most B. cereus isolates are not opportunistic pathogens and only a limited number cause food-borne illnesses, these results demonstrate that some B. cereus strains can cause severe and even fatal infections in patients who appear to be otherwise healthy.